The Diagnostic Value of Neutrophil-Lymphocyte Ratio in Diagnosis of Autism Spectrum Disorders - Nurmalia Purnama Sari; Yudianita K; M. Rafli Haiqal; M. Fadill Akbar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder, progressive disruption of brain development and synaptic connections, which causes impaired communication and behavioral disorders. However, the etiology is unknown. A damaged perinatal environment causes chronic nerve inflammation in genetically susceptible children of ASD, dysregulation of the immune system, which leads to ASD. The ratio of Neutrophil to Lymphocyte (NLR) as one of the markers of inflammation is frequently associated with inflammation-related psychiatric diseases and is potentially used as a diagnostic instrument. A cross-sectional study was carried out from June to November 2019 by using medical records of Outpatients with growth and development disorders and ASD and involving 69 children. The diagnosis of ASD was confirmed by the fifth edition Diagnostic and Manual of Mental Disorders criteria (DSM-V). A routine hematology test was carried out with a flow cytometry method. Diagnostic tests were performed in 43 children with developmental disorders (mean NLR 1.01±0.07) and 26 ASD children (mean NLR 1.02±0.06), with a cut-off value of 0.68. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of NLR were 84.62%; 27.9%; 41.51%; 25%; and 50.2%, respectively. Neutrophil to lymphocyte is sensitive to diagnose ASD but its accuracy is low. Immune dysfunction and complex neurodevelopmental disorders that are affected by chronic inflammation play a role in the occurrence of ASD. Other inflammatory markers are needed to improve the accuracy of laboratory tests to diagnose ASD.